Meningkatkan Kemampuan Berpikir Ilmiah Siswa Menggunakan Model PEMBERANI - Erma Rahmawati; Maimunah (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The problem in this research is the low scientific thinking ability of students in class V science content at SDN Kebun Bunga 6 Banjarmasin. This is because learning is too teacher-centered, students are rarely involved in practical activities or experiments directly, resulting in most students tending to be less active, uncritical, uncreative and have low reasoning power. Lack of interest or interest as well as students' abilities in learning science certainly has an impact on student learning outcomes. The aim of this research is to analyze students' scientific thinking abilities using the BERBERANI Model. This research used a type of classroom action research which was carried out in 4 meetings with 19 students in class V of SDN Kebun Bunga 6 Banjarmasin. The results of the research prove that there is an increase in students' scientific thinking abilities at each meeting, namely at meeting 1 the criteria were "fairly good" with a percentage of 52%, then this increased to 100% classically at meeting 4 with the criteria "Very Good". This shows that the BRAVE model can improve students' scientific thinking abilities.